Sex/gender considerations in school-based interventions to promote children’s and adolescents’ physical activity - Schlund, Annegret; Reimers, Anne Kerstin; Bucksch, Jens; Linder, Stephanie; Demetriou, Yolanda (2021)
Physical inactivity is an increasing problem worldwide, but especially among girls. This difference by gender increases with age. Schools serve virtually all young people in most parts of the world and can thus play an important role in promoting physical activity. In this systematic review, we qualitatively and comprehensively assessed the treatment of sex/gender considerations (from study design to discussion of results) in 56 school-based intervention studies aiming to promote physical activity in children and adolescents. In all 56 studies, the factor of sex/gender was only rudimentarily considered, regardless of the effectiveness of the intervention. The meta-analysis revealed that the interventions had significant but relatively small effects with both girls and boys, along with high heterogeneity. To obtain better information about effective strategies that promote physical activity for both girls and boys equally, researchers conducting future intervention studies should pay attention to sex/gender differences and report on how they take this factor into account.<br
Keywords: Physical activity; School; Children; Adolescents; Gender